Effect of Mixed Cultures of Yeast and Lactobacilli on the Quality of Wheat Sourdough Bread - Xu, Dan; Zhang, Yao; Tang, Kaixing; Hu, Ying; Xu, Xueming; Gänzle, Michael G. (Frontiers in Microbiology, 2019)
In this study, mixed starter cultures of yeast and lactobacilli were used for type I sourdough bread making to evaluate their ability to improve bread quality and increase the amount of flavor volatiles. Kazachstania humilis, Saccharomyces cerevisiae, Wickerhamomyces anomalus, Lactobacillus sanfranciscensis DSM20451T and Lactobacillus sakei LS8 were used in different combinations to ferment wheat sourdough. S. cerevisiae produced the highest amount of CO2 among all strains and thus enhanced bread volume and crumb texture. S. cerevisiae also increased the free thiol level in bread dough, and this study confirms that thiol accumulation was not strongly related to the content of the glutenin macropolymer or bread volume. The role of thiol exchange reactions on bread quality differs between long fermentation sourdough and straight dough with baker’s yeast only. The influence of different starter cultures on wheat sourdough bread volatiles was established by using head space solid-phase microextraction and gas chromatography/mass spectrometry analysis (SPME-GC/MS). The sourdough breads fermented with a combination of lactobacilli and yeast had a more complex profile of volatiles, particularly with respect to esters.